Streptococcus bovis infectious endocarditis and occult gastrointestinal neoplasia: experience with 25 consecutive patients treated surgically. Issue 1 (December 2015) - Alozie, Anthony; Köller, Kerstin; Pose, Lumi; Raftis, Maximilian; Steinhoff, Gustav; Westphal, Bernd; Lamprecht, Georg; Podbielski, Andreas
Abstract To assess the prevalence of gastrointestinal neoplasia in patients withStreptococcus bovis infectious endocarditis we performed a retrospective cohort analysis of all episodes ofS. bovis infectious endocarditis treated at our institution between January 2000 through December 2014. Twenty-five patients were identified for this purpose. 12/25 patients received colonoscopy and 1/25 of the patients was assessed with CT colonography. Of the 13 who underwent colonic assessment, 11 were diagnosed with colonic neoplasms at different stages of development. In the absence of any strong contraindication, gastroenteroscopic evaluation in all patients diagnosed withS. bovis infectious endocarditis should be pursued.